1995
DOI: 10.1111/j.1365-2621.1995.tb05608.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Restructured Beef Steaks Manufactured by Various Techniques

Abstract: Beef (9-l 1% fat) was restructured with each of six mechanical treatments including chunking, fiberizing, slicing, chunking + slicing, slicing + water, and tenderizing each in combination with addition of 0.5% sodium chloride (salt)/0.5% phosphate, 0.5% Na-alginate/O.S% Ca-lactate, 0.5% Na-pectate/O.S% Ca-lactate, or no additives (control). Beef steaks restructured with salt/phosphate had lower (PcO.05) purge losses; higher binding force and bind scores than control products. Steaks restructured with Na-algina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
1
18
0
2
Order By: Relevance
“…Raharjo et al (1995) did not noticed any significant difference in diameter shrinkage of restructured beef steaks formulated with alginates. Dimensional changes were significantly (p<0.05) affected by type of binder used to manufacture restructured steakettes but were not affected by method of size reduction or size opening used to reduce the size of meat (Boles and Shand, 1998).…”
Section: Int J Meat Sci 5 (1): 14-48 2015mentioning
confidence: 95%
See 1 more Smart Citation
“…Raharjo et al (1995) did not noticed any significant difference in diameter shrinkage of restructured beef steaks formulated with alginates. Dimensional changes were significantly (p<0.05) affected by type of binder used to manufacture restructured steakettes but were not affected by method of size reduction or size opening used to reduce the size of meat (Boles and Shand, 1998).…”
Section: Int J Meat Sci 5 (1): 14-48 2015mentioning
confidence: 95%
“…Shand et al (1993) observed significant (p<0.05) highest cooking yield in salt/phosphate structured beef rolls than algin/calcium and controls and ranges of cooking yields were 56.7 to 94.6%. Various mechanical treatments did not affect (p>0.05) cook loss when steaks were restructured using Na-alginate/Ca-lactate or Na-pectate/Ca-lactate (Raharjo et al, 1995). Boles and Shand (1999) found that alginate-bound beef steakettes had significantly (p<0.05) lower cooking loss than fibrimix steakettes.…”
Section: Quality Of Restrucutred Meat Products Cooking Yieldmentioning
confidence: 99%
“…The procedure of tearing and forming has two advantages: (1) it causes less membrane damage, and is less susceptible to oxidation, and (2) the product has more structural integrity and more closely resembles to intact meat cuts in texture (Pearson & Gillett, 1996). Raharjo et al (1995) evaluated quality characteristics of restructured beef by six mechanical treatments. Their results indicated that chunked meat or mixtures of chunked and sliced meats in combination with salt/ phosphate or Na-alginate/Ca-lactate resulted in steaks with acceptable physical and sensory properties.…”
Section: Comminution and Formationmentioning
confidence: 99%
“…Several methods, including use of superior raw material, improvement of processing conditions, and addition of additives, are used to improve the quality of restructured meat products. In part of these, the use of salt and phosphate enhances cohesiveness and cook yield in restructured meat products (Farouk et al, 2000;Raharjo et al, 1995). Schmidt and Trout (1982) reported that restructured meat products using salt and phosphate are related to the thermal binding of myofibrillar protein that is extracted from meat.…”
Section: Introductionmentioning
confidence: 99%